Emergy analysis of three alternative carbon dioxide capture processes. (1st June 2017) - Nimmanterdwong, Prathana; Chalermsinsuwan, Benjapon; Piumsomboon, Pornpote
Abstract: Carbon dioxide (CO2 ) capture technologies have increased in importance recently due to high CO2 emission levels, principally from fossil fuel power generation to support increasing global energy demand. In this study, emergy accounting was applied to quantify the utilization of resources and compare process performance, in terms of sustainability, of three alternative CO2 capture technologies (chemical absorption, solid adsorption and membrane separation) selected from the representative literature. The natural investment or unit emergy value (UEV) of each process was evaluated in units of sej/kg. The results revealed that the lowest to highest UEVs were solid adsorption, membrane separation and amine absorption, respectively. Thus, the most preferable choice for CO2 capture among these three approaches was solid-based adsorption, since it consumed the lowest level of natural resources. Moreover, the UEV of the solid-based adsorption process can be lowered by improving and optimizing the heat utilization within the system and replacing the non-renewable sources of heat and power with renewable resources. In addition, the emergy analysis also provided suggestions for improving membrane separation and amine absorption processes. For amine absorption, improving solvent regeneration efficiency would reduce natural gas consumption, while for membrane separation, power sources should be switched to renewable resources. Highlights: Emergy accounts the process performance in terms of sustainability. Emergy analysis for three alternative CO2 capture processes was evaluated. The solid adsorption process consumed the lowest natural investment. The chemical absorption process used the highest natural investment. The process optimization was proposed to obtain better system sustainability.